Technology External Cause or Individual Internal Cause? Multiple Ways to Improve the Online Learning Effectiveness of Tourism and Hospitality Management Students - Shu-Ning Zhang; Guang-Xiu Jiang; Wen-Qi Ruan; Yong-Quan Li (SAGE Open, 2023)
Online learning platforms have become important learning tools, and online learning replaced face-to-face teaching as the primary learning method of students during COVID-19. However, there have been few systematic studies on learning effectiveness and its influential factors. This study was based on fuzzy-set qualitative comparative analysis (fsQCA) to explore the joint effects of multiple factors on online learning effectiveness for tourism and hospitality students from the dual perspective of the platform and individual. The results revealed five antecedent combinations that led to high-quality online learning, which were categorized into “platform-individual” internal and external promotion paths and “function-interaction” platform environment promotion paths. Moreover, there were substitution effects in the paths to high-quality online learning; specifically, perceived usefulness (PU) and perceived ease of use (PEU) were substitutable, and perceived playfulness (PP), learning attitude (LA), and self-efficacy (SE) could replace each other. Finally, self-efficacy was not a necessary condition for efficient online learning. Our findings highlight substitution relationships among the influencing factors of online learning effectiveness from a configuration perspective and further reveal the internal micromechanisms of achieving high-quality online learning.